Classi medie, democrazia e mercato elettorale - Cuturi, Vittoria (SocietàMutamentoPolitica, 2013)
This paper deals with the problem of political representation of middle class at a time in history when financial crisis and socio-economic insecurity are bringing to a polarization in the distribution of wealth, undermining middle-class status and aspirations. In western countries, some political leaders of left wing parties have adopted the triangulation strategy (as theory or as method) to secure middle-class votes. How far such a choice is feasible and accepted in Italian country.